Morpho‐anatomical characterization of Eryngium yuccifolium ('Rattlesnake‐master'). Issue 1 (9th August 2021) - Raman, Vijayasankar; Manfron, Jane; Khan, Ikhlas Ahmed
Abstract: This paper provides detailed morpho‐anatomical and histochemical characteristics of the leaves, peduncles, stems, and roots of Eryngium yuccifolium Michx. (Apiaceae) by bright‐field light and scanning electron microscopy. Noteworthy morpho‐anatomical features include the monocot‐like leaves with parallel venation and distant marginal bristles, amphistomatic leaves with paracytic or anisocytic stomata and heterogenous isobilateral mesophyll, the presence of epicuticular wax crystalloids on both leaf surfaces, calcium oxalate druses and secretory canals in all the studied plant parts, presence of hypodermis, stem and peduncle with longitudinal ribs containing collenchyma, presence of aerenchyma in the peduncle and root, and absence of sclerenchyma in all the plant parts analyzed. These characteristics would aid in the taxonomy, species identification as well as quality control of the botanical. Abstract : Anatomy of Eryngium yuccifolium is illustrated with light and scanning electron microscopy This dicot plant has monocot‐like leaves with parallel venation The leaves are isobilateral and amphistomatic Epicuticular wax crystals are found on both epidermises Sclerenchyma is absent; collenchyma is the primary mechanical tissue